Investing In the Reuse of Treated Wastewater - Scott, Chris; Darghouth, Salah; Dinar, Ariel (World Bank, Washington, DC, 2012)
Of the projected 1 billion growth in global population by 2015, 88 percent will take place in cities, nearly all of it in developing countries. Investments in urban water supply and sewerage coverage are rising. However, adequate treatment for agricultural reuse with acceptable risk mitigation for human health and the environment will require further investment. While this Investment Note addresses reuse after treatment, it is critical to ensure that investments in treatment appropriate for reuse schemes will be made. Urban wastewater is well suited to agricultural reuse and landscaping because of the reliability of supply, proximity to urban markets, and its nutrient content. To have an impact on scarcity, reuse of wastewater must substitute for, not add to, existing uses of higher-quality water. Moreover, reuse of treated wastewater often disproportionately benefits the poor. It must be combined with strategies to prevent or mitigate health risks from pathogens, heavy metals, pesticides, and endocrine disrupters, and environmental damage from heavy metals and salinity. Long-term institutional coordination among urban, agricultural, and environmental authorities and end users is a requirement for water reuse investments to pay off. This note outlines technological and management interventions suitable for World Bank lending.